2002
DOI: 10.1128/jb.184.23.6566-6571.2002
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis of the Heat Shock Regulator HrcA ofChlamydia trachomatis

Abstract: HrcA is a regulator of bacterial heat shock gene expression that binds to a cis-acting DNA element called CIRCE. It has been proposed that HrcA and CIRCE function as a repressor-operator pair. We have purified recombinant HrcA from the pathogenic bacterium Chlamydia trachomatis and have shown that it is a DNAbinding protein that functions as a negative regulator of transcription. HrcA bound specifically to the CIRCE element in a concentration-dependent manner. HrcA repressed the in vitro transcription of a chl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
75
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(78 citation statements)
references
References 26 publications
2
75
0
1
Order By: Relevance
“…As indicated in Fig. 7, chlamydial HrcA readily interacts with the promoter region of dnaK of M. genitalium (lane 2), which was comparable to the interaction between chlamydial HrcA and its own dnaK promoter (lane 2) (46). Moreover, the addition of unlabeled competitors markedly reduced the DNA-protein complex formation (lanes 3).…”
mentioning
confidence: 77%
“…As indicated in Fig. 7, chlamydial HrcA readily interacts with the promoter region of dnaK of M. genitalium (lane 2), which was comparable to the interaction between chlamydial HrcA and its own dnaK promoter (lane 2) (46). Moreover, the addition of unlabeled competitors markedly reduced the DNA-protein complex formation (lanes 3).…”
mentioning
confidence: 77%
“…The location of the Group III chaperonin downstream of the hrcA suggested that Group III CPNs could be HrcA regulated. The Group I CPN and Hsp70s of many bacteria are HrcA regulated (27)(28)(29)(30). In silico analysis revealed the presence of a CIRCE consensus site upstream of the HrcA as well as the Group I CPN in these genomes (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Knowledge of the extent to which the regulation of transcription contributes to the chlamydial life cycle has been limited, in part, by the lack of suitable experimental tools. In this regard, only a handful of transcription inhibitors (21)(22)(23)(24)(25) and three transcription activators (26)(27)(28) had been identified in chlamydiae before our study. Our work identifies GrgA as a previously undocumented transcription factor in C. trachomatis.…”
Section: Discussionmentioning
confidence: 99%